تدخل الدولة في تعويض المضرور جسمانيا بين الأصل والاحتياط - بن أوذينة, أمحمد; بن قويدر, زبيري (جامعة الوادي University of Eloued, 2019)
نحاول في ثنايا هذا المقال استجلاء الظروف التي جعلت المشرع الجزائري يغيّر نظرته لمسألة التعويض عن الأضرار الجسمانية والتعاطي مع هذه المسألة باهتمام، باعتبارها تمس بأغلى شيء عند الإنسان وهي السلامة الجسدية. كما نبرز أهم الأنظمة التعويضية المستحدثة أو التشريعات الخاصة التي تعدّ كبديل أو كمكمل لقواعد المسؤولية المدنية، في خضم ذلك نستطلع أهم مظاهر تدخل الدولة في دواليب التعويض عن الأضرار الجسمانية؛ سواء تدخلها بشكل أصلي عبر مختلف صناديق الضمان أو عبر الميزانية العامة، وسواء بتدخلها بشكل احتياطي عن طريق الشريعة العامة مجسّدة في المادة 140مكرر1 من القانون المدني المعدّل والمتمّم أو عن طريق صندوق ضمان تعويض السيارات. In this article, we attempt to clarify the circumstances that made the Algerian legislator change his view about the issue of compensation for the physical harm and to deal with this issue with interest, as it touches the most precious thing for the human ,which is his physical safety. We also highlight the most important innovative compensatory systems that are considered as an alternative or complement to the rules of civil responsibility. In the midst of that, we examined the most important manifestations of the state’s intervention in the tires of compensation for physical harm; whether its intervention in an original manner through the various funds of guarantee or through the general budget.And also its intervention in a substituent manner through the general legislation, which it mentioned in Article 140 bis1 of the modified and complemented civil law or through the tires of compensation guarantee of cars.
Keywords: التعويض ; الأضرار الجسمانية ; التشريعات الخاصة ; الأنظمة الخاصة ; صناديق الضمان